Performance, Carcass Traits, and Body Composition of Broilers Fed Different Linseed Oil Levels between 21 and 56 Days of Age - Duarte, K. F. [UNESP]; Junqueira, O. M.; Borges, L. L. [UNESP]; Rodrigues, E.; Filardi, R. da S. [UNESP]; Praes, M. F. F. M. [UNESP]; laurentiz, A. C. de [UNESP]; Domingues, C. H. de F. [UNESP] (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2014)
This study was carried out to evaluate the effect of the inclusion of different linseed oil levels (0.0, 3.3, 6.6, or 9.9%) in iso-energy diets fed during the period of 21 to 56 days of age on the performance, carcass traits, and body composition of broilers. A total of 1,600 broilers were distributed according to a completely randomized experimental design consisting of four treatments with eight replicates of 40 birds per experimental unit. In the period of 21-42 days of age, weight gain increased, feed and calorie conversion ratios quadratically improved, and feed and metabolizable energy intakes linearly increased as dietary linseed oil level increased. Considering the entire experimental period, dietary linseed oil linearly increased weight gain and feed and energy intakes, and feed and calorie conversion ratios in a quadratic manner. On days 42 and 56, abdominal fat percentage and carcass yield were quadratically influenced by dietary linseed oil. Total body fat content at 56 days of age was quadratically influenced by dietary linseed levels.
Keywords: Ether extract; weight gain; abdominal fat; crude protein; carcass yield